Biochemical Study of Mumijo in Uvs province, Mongolia - Sukhdolgor, J; Orkhonselenge, D (Mongolian Journal of Chemistry, 2014)
The authors cleared mumijo by extractive and distil methods, defined pure output of natural mumijo and compared difference between these two methods. We defined the amount of dry and extractive substances, raw oil, antioxidant-rutin, vitamin C, fulvic acid, common nitrogen and total protein, content of protein amino acids, and mineral elements in natural mumijo. We exposed 13 protein amino acids in sample of natural mumijo. The content of total irreplaceable amino acids (5) were 26.2%. The authors defined macro and microelements (42) in ash of natural mumijo. In sample of mumijo exposed 10 elements are oxide form, W, Y, Cs, La-rare metal of the earth, and actinoids- Nd, Th, U; lantanoids-Pr, Sm. The same exposed non-ferrous metal-Cu, Mo; light metal-Al, mixed metal-Pb, Zn. However, the valuable metals-Au, Ag and white gold are not exposed. DOI: http://dx.doi.org/10.5564/mjc.v12i0.173 Mongolian Journal of Chemistry Vol.12 2011: 56-59